Pharmacokinetics and Safety of Macrocyclic Gadobutrol in Children Aged Younger Than 2 Years Including Term Newborns in Comparison to Older Populations. Issue 1 (January 2016) - Kunze, Christian; Mentzel, Hans-Joachim; Krishnamurthy, Rajesh; Fleck, Robert; Stenzel, Martin; Bhargava, Ravi; Burrowes, Delilah; Sutter, Gabriele; Schultze-Mosgau, Marcus; Santiuste, Marta; Hahn, Gabriele
Abstract : Objectives: This clinical study evaluated the pharmacokinetics (PK) and safety data of macrocyclic extracellular contrast agent gadobutrol in pediatric subjects aged younger than 2 years. Materials and Methods: Pediatric subjects (term newborns to those aged younger than 2 years) with normal renal function undergoing magnetic resonance imaging with gadobutrol (0.1 mmol/kg body weight [BW]) were prospectively enrolled in this open-label, multicenter clinical trial to evaluate PK as a primary end point. Plasma PK was analyzed using a population-based PK approach. Safety and qualitative efficacy (evaluation of images) were secondary end points. Safety and tolerability were assessed throughout study participation (approximately 7 days). Imaging efficacy variables were assessed by investigators. Results: Forty-four subjects were evaluated for safety and efficacy; 43 subjects were eligible for PK evaluation including 9 term newborns and infants aged younger than 2 months. Gadobutrol PK in pediatric subjects aged younger than 2 years were adequately described by a linear 2-compartmental model with elimination from the central compartment. Total median systemic exposure (area under the curve) of gadobutrol was estimated at 776 μmol · h/L (range, 544–1470 μmol · h/L). Simulated median concentration at 20 minutes after injection of gadobutrol (C20 ) was 339 μmol/L (range, 230–456 μmol/L). Safety and tolerability profile were similar to older populations. In 1 subject (2.3%), vomiting was reported as a mild adverse event related to gadobutrol, and there were no reported serious adverse events. The evaluation of gadobutrol-enhanced images provided improved diagnosis, increased confidence in diagnosis, and contributed to subject clinical management. Conclusions: The PK profile of gadobutrol in children aged younger than 2 years including newborns is similar to that in older children and adults. At the dose of 0.1 mmol/kg BW, gadobutrol had a favorable safety profile and was well tolerated with similar profile across the age range 0 to younger than 2 years and compared with older children and adults. Extrapolation of efficacy data from adults to the younger pediatric population, including term newborns, is justified. The recommended standard dose of gadobutrol (0.1 mmol/kg BW), as used in the population aged 2 years and older, is also appropriate in children aged younger than 2 years.